The Influence of Near- and Far-field Earthquakes on the Seismic Performance of Base-Isolated Nuclear Power Plant Structures - Tran, V. B.; Nguyen, S. M.; Nguyen, T. H.; Nguyen, V. H.; Doan, T. T. H.; Nguyen, D. D. (Engineering, Technology & Applied Science Research, 2022)
This study aims to investigate the influence of near- and far-field earthquakes on the seismic performance of base-isolated Nuclear Power Plant (NPP) structures. Two earthquake motion groups of near-field and far-field characteristics are selected for fragility evaluation analysis. A base-isolated advanced reactor power 1400 (APR-1400) is employed for numerical analysis. A set of fragility curves are derived for various limit states based on the maximum likelihood estimation. The limit states are defined in terms of Lead Rubber Bearing (LRB) deformation capacity. The numerical results reveal that the median maximum deformations of LRBs were smaller for far-field ground motions than for near-field motions. Also, the comparison of fragility curves demonstrates that the probability of failure of base-isolated NPP structures is higher for near-field ground motions than far-field motions. It is crucial to select earthquake ground motions with both near- and far-field motions for the seismic evaluation of NPP structures.